2016
DOI: 10.1186/s12935-016-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous electromagnetic forces emissions during cell respiration as additional factor in cancer origin

Abstract: BackgroundSeven decades ago, a seminal paper by Dr. Denham Harman in (J Gerontol 11(3):298–300, 1956), introduced a theory stating that there are good reasons for assuming that endogenous irradiation in the living cells could lead to cancer via an obscure mechanism. The main purpose of this manuscript is to shed some light in said mechanism by proposing a five-step eukaryotic cell cancer triggering cycle. In other words, a new factor is introduced, namely the recently found emissions of electromagnetic forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…CAT is added during the processed food manufacturing for esthetic reasons, to avoid the "bleaching effect" by hydrogen peroxide. Supporting the hypothesis are prior experiments linking electromagnetic fields (EMFs) emissions during cell respiration, as causing DNA damage and triggering cancer genesis (2,3). In those papers (CAT) was briefly reported to emit electromagnetic fields (EMFs).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…CAT is added during the processed food manufacturing for esthetic reasons, to avoid the "bleaching effect" by hydrogen peroxide. Supporting the hypothesis are prior experiments linking electromagnetic fields (EMFs) emissions during cell respiration, as causing DNA damage and triggering cancer genesis (2,3). In those papers (CAT) was briefly reported to emit electromagnetic fields (EMFs).…”
Section: Introductionmentioning
confidence: 88%
“…Also shown, were metabolic disruptions of fronted hair follicles when imbedded in a diamagnetic (repulsive) solution (10). As aforementioned, EMFs emitted during cell respiration were proposed to be an additional factor in cancer genesis as cited in (3).…”
Section: Experiments Supporting the Hypothesismentioning
confidence: 99%
“…The hair has been classified as a mini organ with its own circulation, nerve innervation and cellular divisions (6), this entails cellular respiration inducing H2O2 decomposition. Cell respiration entails the elimination of toxic substances, one of them being the endogenously produced H2O2 (7,8). Experimentally, when drops of H2O2 are in contact with plucked hair follicles on a glass slide, there is an explosive reaction seen due to H2O2 breakdown into water and oxygen molecules; therefore this maneuver obscures any time related details of the reaction (Figure 2).…”
Section: The Injured Hair Root Experimentsmentioning
confidence: 99%
“…The main purpose of this manuscript is to demonstrate the role of the paramagnetic oxygen molecule effects on human cells structural deformations of both eukaryotic and prokaryotic types, these findings could confirm or support a previously published a biophysical cancer origin hypothesis. In a 2016 publication, the electromagnetic fields (EMFs) from the decomposition of H2O2 molecules by antioxidants during cell respiration was hypothesized as an additional factor in cancer origin (1). Prior research has shown that when air bubbles are ruptured, shock waves energy is released.…”
Section: Introductionmentioning
confidence: 99%